Μελέτη περίπτωσης ενήλικης με εμπειρία εκφοβισμού κατά τη διάρκεια της σχολικής της φοίτησης - Α Μαυροειδή; Γαλανάκη, Ε. (Τετράδια Ψυχιατρικής, 2011)
The purpose of this case study is the presentation of the adverse long-term consequences of school bullying. This case study concerns a 22-year-old female who sought out therapy in order to cope with her intense negative feelings of stress and depression. During the therapeutic process, it became clear that the patient's current problems were related to having been the victim of systematic bullying during her school years. Her self-image in the period she sought out help deteriorated, as shown in her negative cognitions regarding her abilities and capacities, which had been shaped under the influence of the bullying experience. According to a number of empirical investigations (Hawker & Boulton, 2000; Nansei, Craig, & Overpeck, 2004; Kochenderfer & Ladd, 1996; Kochenderfer & Wardrop, 2001; and in Greece: Galanaki & Vogiatzoglou, 2007; Galanaki, Amanaki, & Noikokiri, 2009), some of the consequences of school bullying - such as relationship problems, low self-esteem, limited social contacts, stress, depression, feelings of loneliness - are likely to be maintained for an extended period of time, especially when the individual has failed to form a network of social support (Newman, Holden, & Delville, 2004). Thus, adults who as pupils suffered from bullying experience more feelings of loneliness, depression, and inadequacy and they encounter difficulties in their interpersonal relations (Gilmartin, 1987; Hugh-Jones & Smith, 1999; Isaacs, Hodges, & Salmivalli, 2008; Newman et al., 2005; Olweus, 1994; Storch, Roth, Cales, Heimberg, Bravata, & Moser, 2004). In this case study, the ongoing presence and lasting influence of these negative consequences in adult life become obvious.